2019
DOI: 10.1101/646380
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

miR-26a regulates extracellular vesicle secretion from prostate cancer cells via targeting SHC4, PFDN4 and CHORDC1

Abstract: AbstractExtracellular vesicles (EVs) are known to be involved in intercellular communication during cancer progression; thus, elucidating the detailed mechanism will contribute to the development of a novel strategy for EV-targeted cancer treatment. However, the biogenesis of EVs in cancer cells is not completely understood. MicroRNAs (miRNAs) regulate a variety of physiological and pathological phenomena; thus, miRNAs could regulate EV secretion. Here, we performed high-throug… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
(11 reference statements)
1
7
0
Order By: Relevance
“…In recent years, the involvement of extracellular vesicles in tumor progression and metastasis has been extensively studied. However, the mechanism of EV secretion in tumors is still unknown [4,7,37]. Our experiments confirmed that LINC00511 markedly induced the production of MVBs and the release of exosomes in liver cancer and promoted the invasion of HCC.…”
Section: Discussionsupporting
confidence: 66%
“…In recent years, the involvement of extracellular vesicles in tumor progression and metastasis has been extensively studied. However, the mechanism of EV secretion in tumors is still unknown [4,7,37]. Our experiments confirmed that LINC00511 markedly induced the production of MVBs and the release of exosomes in liver cancer and promoted the invasion of HCC.…”
Section: Discussionsupporting
confidence: 66%
“…With respect to PCa, potential exosomal biomarkers derived from serum or urine for diagnosis have been widely investigated (Cho et al., 2019; Hao et al., 2015). Interestingly, recent studies showed miRNAs, with potential clinical implications for cancer therapy, are involved in EV secretion from prostate cancer (PCa) cells (Urabe et al., 2020; Urabe et al., 2020). However, only a few functional studies on extracellular vesicles have been conducted to delineate whether PCa exosomes can mechanistically influence bone metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…EVs from the culture medium were isolated by a differential ultracentrifugation (UC) [13,15]. Cells were transplanted into 10 cm plates and changed DMEM with 10% EV-depleted FCS.…”
Section: Ev Isolation and Identificationmentioning
confidence: 99%
“…Recent studies have reported that miRNA could regulate EV secretion to keep itself steady-state level. For instance, miR-26a has been found to be related to EV secretion, resulting in the inhibition of prostate cancer progression [13]. Besides, the relationship between EV secretion and reprogrammed metabolism in cancer cells has not been identified before.…”
Section: Introductionmentioning
confidence: 99%